2019
DOI: 10.1186/s12885-019-5894-8
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the 8th edition UICC/AJCC TNM staging system for HPV associated oropharyngeal cancer patients managed with contemporary chemo-radiotherapy

Abstract: Background To compare outcomes of high-risk human papilloma virus-related oropharyngeal squamous cell carcinoma (HPV OPSCC) treated with modern radiation treatment (RT) and daily image-guidance, staged with the 7 th versus the 8 th Edition (Ed) Union for International Cancer Control (UICC)/American Joint Committee on Cancer (AJCC) TNM staging systems. Methods All eligible patients with HPV OPSCC treated definitively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…Currently, according to the 8th edition of the American Joint Committee on Cancer (AJCC) Cancer Staging Manual, OPSCC is classified into two different phenotypes, according to the expression of p16 [34]. HPV-related OPSCC patients are considered to be a unique group.…”
Section: The Association Between Hpv and Opsccmentioning
confidence: 99%
“…Currently, according to the 8th edition of the American Joint Committee on Cancer (AJCC) Cancer Staging Manual, OPSCC is classified into two different phenotypes, according to the expression of p16 [34]. HPV-related OPSCC patients are considered to be a unique group.…”
Section: The Association Between Hpv and Opsccmentioning
confidence: 99%
“…Human papillomavirus (HPV) status is the only molecular stratifier used routinely in current clinical practice [ 5 ] (mostly identified by using p16 expression as a surrogate marker) and is the single most significant non-anatomical prognostic marker [ 6 ]. Despite a higher incidence of positive lymph node involvement at presentation, which tended to skew staging information in the American Joint Committee on Cancer (AJCC) 7th Edition Manual towards advanced disease [ 7 ], patients with HPV +ve tumours have repeatedly been shown to have improved disease-free and overall survival compared to those with HPV −ve disease [ 8 , 9 , 10 ], although notably, a significant subset have more aggressive disease with poor clinical outcome [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who were AJCC 7 stage III became AJCC 8 stage I 73% of the time, stage II 24% of the time, and III 3% of the time. 23 Mizumachi et al did the same with a cohort of 111 patients and found that patients who were AJCC 7 stage IV became AJCC 8 stage I 56% of the time, stage II 20% of the time, and stage III 24% of the time. Patients who were AJCC 7 stage III became AJCC 8 stage I 47% of the time, and stage II 53% of the time.…”
Section: Discussionmentioning
confidence: 99%